Identification of zygotic and nucellar seedlings in polyembryonic mango cultivars - Martinez Ochoa, Elisa del Carmen; Andrade-Rodríguez, Maria; Rocandio Rodríguez, Mario; Villegas Monter, Angel (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the occurrence of polyembryony in the mango cultivars Manila and Ataulfo, and to determine whether seedlings cultured in vitro are zygotic or nucelar. Percentage of polyembryony was calculated and the number of embryos in 100 seeds of each cultivar was recorded. 'Manila' exhibited 97% polyembryony with 3.4 embryos per seed, while 'Ataulfo' had 95% polyembryony with 3.2 embryos per seed. Later, 20 seeds of each cultivar were established in vitro, and it was analyzed those in which all embryos germinated (12 seeds from 'Manila' and 7 from 'Ataulfo'). DNA was extracted from seedling leaf tissue, and its origin was identified with 14 RAPD primers. The polymorphic markers recognized the seedlings of sexual origin in seven of nine 'Manila' polyembryonic seeds, and in four of seven 'Ataulfo' ones. Also, in polyembryonic seeds not all zygotic seedlings were produced by small embryos located at the micropyle.